(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: In India, most of the deaths among children (<5 years) are attributed to food and water contamination. Mothers are usually the final line of defence against food-borne illnesses. Thus, the role of mothers in ensuring food safety at home is well accepted. Food safety is a significant public health issue, as it aims to prevent or control foodborne illnesses. Aim: To assess and evaluate knowledge, attitude, and practice towards food safety practices and associated factors among mothers of under-five children in Tirupati. Methodology: A community-based, analytical, cross-sectional study was conducted among mothers of children under 5 years in Tirupati over 2 months. A total of 110 mothers were interviewed using a semi-structured questionnaire that included sociodemographic details and questions on knowledge, attitudes, and practices (KAP) regarding food safety. The association between KAP and sociodemographic factors was assessed using appropriate statistical tests. Results: The mean age of the mothers was 26.76 (3.12) years. Mothers with good knowledge of food safety were 68.2%, mothers with a good attitude towards food safety were 48.3%, and mothers with good practices were 35.8%. Education, Socioeconomic status, good food safety knowledge, and attitude were significantly associated with good food safety practices. Conclusions: About one-third of the mothers in the study area had poor food safety practices. Educational status, income, food safety knowledge, and food safety attitude were significantly associated with mothers’ food safety practices. Food hygiene attitudes, knowledge, and education levels should be enhanced to improve food safety practices among mothers responsible for household food preparation.